Counting publications and citations is not just irrelevant: it is an incentive that subverts the impact of clinical research - Büttner, F.; Ardern, C. L.; Blazey, P.; Dastouri, S.; McKay, H. A.; Moher, D.; Khan, K. M. (British Journal of Sports Medicine, 2021)
More than one million scientists publish peer-reviewed research each year.1 Health research strives to generate new discoveries or consolidate existing knowledge to benefit the lives of humans. But does published health research impact patients, policy, the economy, or society?